From Birth through Transition to Maturation: The Evolution of Technology‐Based Alliance Networks. Issue 2 (18th September 2015) - Gilsing, Victor; Cloodt, Myriam; Roijakkers, Nadine
Abstract : This article considers the evolution of interfirm networks within a context of technological change. More specifically, it studies the evolution of structural and positional embeddedness in a network of technology‐based alliances when it moves from an early period of invention creation to a subsequent period of new product development and commercialization. Empirically, we study the evolution of technology‐based alliance networks in the biopharmaceutical industry over a period of about 25 years, from 1975 until 1999. Examining interorganizational networks over such an extended time period allows us to move beyond more static approaches that have characterized most network studies until now, and consider network evolution along its various phases of birth, growth, and early maturation instead. Our findings indicate that the evolution of both structural and positional embeddedness does not follow the common idea of a path of linear progression, but instead strongly exhibits nonlinearity by resembling a sigmoid pattern. These findings have a number of implications. First, the break in the process of linear progression contrasts with the standing literature that (implicitly) assumes the informational and resource value of a network structure to remain constant over time or to evolve linearly from carrying low value to progressively higher value. Instead, our finding that the evolution of structural and positional embeddedness is nonlinear echoes the speculative idea, as expressed by Gulati and Garguilo, that network change may possibly be nonlinear when seen over the long run. A second implication concerns the validity of standing insights from the social network literature such as Coleman's theory of social capital and Burt's theory of structural holes. These theories may not apply to the extent that there are strong changes in environmental conditions like environmental uncertainty and/or munificence, such as during a transition phase as considered in this study.